The Development of an Egg Incubator Prototype with the Use of Heat on the Condenser Side of the Refrigerator - Budiastawan, Ngurah Putu; Wiratmaja, I Gede; Nugraha, I Nyoman Pasek (International Journal of Mechanical Engineering Technologies and Applications, 2022)
The development for an egg incubator prototype with the use of heat on the condenser side of the refrigerator belongs to  Research and Development (R&D) conductment with the aim of knowing the process of developing an egg incubator prototype by using heat on the condenser side of the refrigerator to find out the feasibility  level. The method in this study uses Quality Function Deployment (QFD), which is a method used in the early stages of product design and development that makes quality design of a product based on the market quality demand and order of the customer. The prototype development process undergo  several stages, including: preliminary survey to the farmer community, design, instrument validity testing, prototype making, media export testing and small group testing. Based on the calculation of the results of the validity test assessment by the instrument content expert, the content validity value of 1 which refers to the instrument validity criteria table is included in the very high validity criteria. Furthermore, based on the calculation of the validation results from the media expert test and the small group test, it gets a percentage of 100% for the media expert test and a percentage of 95.20% for the small group test and refers to the eligibility level qualification table with a scale of 5 in the very appropriate category without the need for revision, so that the  developed prototype egg incubator  are suitable for use and marketable for the industry.